Prosocial behaviour in adolescents : classroom and sport specific environments : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Albany, New Zealand - Baudinet, Olivia (Massey University, 2013)
Research has found that participation in sports is positively associated with physical health, academic achievement, and social wellbeing. New Zealand lacks studies in this area, particularly in an intermediate school-aged population. For this reason, the purpose of the current study was to examine prosocial behaviour between two major educational contexts to determine if the change in environment had an effect on the self-reported social behaviour perceived of students. A group of 175 males and females aged 10 -12 years participated in the research. The sample attended a public intermediate school on Auckland’s North Shore. Data collection was undertaken on the school premises, through administration of anonymous self-report questionnaires engaging perceived social behaviours including self-efficacy, altruism, empathy, aggression, and prosocial behaviour. The results were interpreted in the context of Bandura’s (1991a) social cognitive theory of moral behaviour. Confirmatory factor analysis was employed to initially assess the fit of the data. Psychometric evaluations found that measures exhibited adequate internal consistency, and adequate fit of the data to the models. Following preliminary analyses, the two contexts in which prosocial behaviour was measured were retained as the focus in multiple regression analyses, utilising given predictor variables. Regression analysis tested found Altruism and Social-Efficacy to be important predictors of prosocial behaviour, whereas Cooperation, Social-Efficacy, and Helping found to contribute to aggression. Hypothesis testing suggested that physical context did not account for significant differences in prosocial behaviour. However, aggression was affected by a change in physical context. Gender was seen to produce effects, with significant differences noted between the classroom and physical education settings when comparing male, though no differences were found when comparing females between contexts. Limitations and implications for future research are discussed.
Keywords: Preteens; School children; Social interaction in children; Moral development; Prosocial behaviour